The role of anxiety and trauma in predicting school avoidance among students: a structural equation modeling analysis - Wang, Haoyu; Qin, Qixiu (Frontiers in Psychology, 2025)
This study investigated how anxiety and traumatic experiences contribute to adolescents’ school avoidance by constructing a dual-path mediation model. In this model, emotion regulation was tested as a mediator linking anxiety to school avoidance, while psychological resilience was examined as a mediator linking traumatic experiences to school avoidance. A total of 500 school students from eastern China participated in the survey. Structural equation modeling (SEM) was used to analyze the direct and interactive effects of the two risk factors, assess two mediating pathways, and investigate potential group differences by gender and grade level. The research employed a combination of methods—including questionnaire surveys, descriptive statistics, correlation analysis, multiple regression, and model fitting—to comprehensively evaluate five key variables: anxiety, trauma, emotion regulation, resilience, and school avoidance. The results showed that both anxiety and traumatic experiences were significant predictors of school avoidance, and their interaction further intensified avoidance behavior. Emotion regulation partially mediated the effect of anxiety on school avoidance, while psychological resilience served as a protective mediator between trauma and avoidance. This study is the first to integrate anxiety and trauma into a single analytical framework, highlighting the complex interactions between risk and protective factors. It also contributes new empirical insights into gender and grade-level variations. These findings underscore the importance of incorporating emotion regulation and resilience-building strategies into school curricula and teacher training programs. This study is the first to place anxiety and trauma within a single analytical framework, underscoring how risk and protective factors interact to shape school avoidance. It further offers empirical evidence of variations by gender and grade level. Taken together, the results highlight the value of incorporating emotion regulation and resilience training into school curricula and teacher preparation, while also providing a solid foundation for developing more precise and sustainable school-based mental health services.